(untitled) (Journal of Pathology of Nepal, 2013)
Background: Ovarian cancers are common among females. The ovarian tumors are classified according to its histogenesis. In the present study, we analyzed the germ cell ovarian tumors reported in our institute. Materials and Methods: This study was a hospital based retrospective study. All ovarian germ cell tumor reported from Jan 2001 to Feb 2013 were retrieved and analyzed. The specimens were routinely processed and the slides were stained with H&E and special stains wherever required. Results: A total of 340 cases of ovarian tumors were reported and 150 cases (44%) were of germ cell origin. We had 137 cases of benign and 13 cases of malignant germ cell tumors. Most common subtype was mature cystic teratoma comprising 125 cases. Among the malignant cases, the most common was immature teratoma (5 cases). Age range in our series was from 8 to 82 years (mean 28 years). The most common age group affected was 21-30 years. Most of the malignant cases (76.9%) were in less than 30 years. Among the malignant cases majority (84.6%) were more than 10 cm in size. None of the malignant germ cell tumors were bilateral. Conclusion: Among germ cell tumors of ovary, mature cystic teratoma is the most common tumor and malignant subtypes are uncommon. Malignant tumors tend to occur in younger age group. DOI: http://dx.doi.org/10.3126/jpn.v3i6.8990 Journal of Pathology of Nepal (2013) Vol. 3, 441-446